Motivations associated with non-disclosure of self-reported concussions in former collegiate athletes - Kerr, Zachary Y. (Am J Sports Med, 2015)
BACKGROUND: Previous studies examining non-disclosure among athletes in various settings have found substantial proportions of athletes with undisclosed concussions. Substantial gaps exist in our understanding of the factors influencing athletes’ disclosure of sports-related concussions. HYPOTHESIS/PURPOSE: This cross-sectional study examined prevalence of, and factors associated with, non-disclosure of recalled concussions in former collegiate athletes. STUDY DESIGN: Cross-sectional survey. METHODS: Former collegiate athletes (n=797) completed an online questionnaire. Respondents recalled self-identified sports-related concussions (SISRC) that they sustained while playing sports in high school, college, or professionally, and whether they disclosed these SISRC to others. Respondents also recalled motivations for non-disclosure. We computed the prevalence of non-disclosure among those who recalled SISRC. Multivariate binomial regression estimated adjusted prevalence ratios (PR) with 95% confidence intervals (CI) controlling for sex, level of contact in sport, and year began playing college sports. RESULTS: Two-hundred-and-fourteen (26.9%) respondents reported sustaining at least one SISRC. Of these, 71 (33.2%) reported not disclosing at least one SISRC. Former football athletes were most likely to report non-disclosure (68.3% of those recalling SISRC); female athletes who participated in low/non-contact sports were the least likely to report non-disclosure (11.1% of those recalling SISRC). The prevalence of non-disclosure was higher among males than females in the univariate analysis, (PR=2.88; 95%CI: 1.62, 5.14) multivariate analysis (PR=2.11; 95%CI: 1.13, 3.96), and multivariate analysis excluding former football athletes (PR=2.11; 95%CI: 1.12, 3.94). The most commonly reported motivations included: did not want to leave the game/practice (78.9)%; did not want to let the team down (71.8%); did not know it was a concussion (70.4%); and did not think it was serious enough (70.4%). CONCLUSION: Consistent with previous studies, a substantial proportion of former athletes recalled SISRC that were not disclosed. Males were less likely to disclose all their SISRC than females.